(untitled) (Journal of Business Management and Accounting, 2023)
COVID-19 pandemic has changed and forced many parties, including individuals and business organizations, to alter their lifestyles, business patterns and working arrangement. Consequently, this situation cause majority of businesses to implement work from home (WFH) to the employees to ensure the business operations can operate continuously and sustainably. This study is conducted to explore the drivers that contributes to working from home preferences during covid-19 pandemic among engineers in manufacturing company. Specifically, this study examines the work environment, work-life balance, job satisfaction and performance, and work from home preferences. This study employed a purposive sampling technique with several inclusion criteria and was quantitative by using a survey involving 172 engineers in the manufacturing company. The study findings revealed that work environment and work-life balance significantly influence work from home preferences while job satisfaction and job performance are vice versa. This study also highlights the study implications, limitations, and possible future studies.